ANALYSIS OF MADRASAH POLICY IN THE INDONESIAN NATIONAL EDUCATION SYSTEM - Safuroh Mulyadi; Devi Fatwanti; Abdul Muin; Aceng Hasani (Cakrawala Pedagogik, 2026)
Madrasah is a formal educational institution with Islamic characteristics that is part of the national education system in Indonesia. The existence of madrasah not only functions as a religious educational institution, but also as a provider of general education integrated with Islamic values. This study aims to analyze the implementation of policies challenging madrasah in the national education system, opportunities and challenges of madrasah in Indonesia, efforts to strengthen madrasah policies. This study uses a library method through a qualitative descriptive approach by reviewing laws and regulations and policy documents related to madrasah. The results of the study indicate that madrasah policies in Indonesia continue to develop towards strengthening legality, improving quality, modernizing the curriculum, and institutional governance. However, its implementation still faces challenges in the form of disparities in quality, limited infrastructure, and the quality of human resources. Meanwhile, efforts to strengthen madrasah policies can be done by strengthening the distribution of aid facilities and financing, improving the competence of teachers and madrasah principals, strengthening the implementation of an integrative curriculum between general knowledge, religious knowledge, character, and 21st-century skills, and improving accountability-based governance and service quality. Therefore, madrasah policies need to be continuously strengthened to be able to respond to national education demands and community needs.